A Room‐Temperature Spin‐Valve with van der Waals Ferromagnet Fe5GeTe2/Graphene Heterostructure. Issue 16 (8th March 2023) - Zhao, Bing; Ngaloy, Roselle; Ghosh, Sukanya; Ershadrad, Soheil; Gupta, Rahul; Ali, Khadiza; Hoque, Anamul Md.; Karpiak, Bogdan; Khokhriakov, Dmitrii; Polley, Craig; Thiagarajan, Balasubramanian; Kalaboukhov, Alexei; et al.
Abstract: The discovery of van der Waals (vdW) magnets opened a new paradigm for condensed matter physics and spintronic technologies. However, the operations of active spintronic devices with vdW ferromagnets are limited to cryogenic temperatures, inhibiting their broader practical applications. Here, the robust room‐temperature operation of lateral spin‐valve devices using the vdW itinerant ferromagnet Fe5 GeTe2 in heterostructures with graphene is demonstrated. The room‐temperature spintronic properties of Fe5 GeTe2 are measured at the interface with graphene with a negative spin polarization. Lateral spin‐valve and spin‐precession measurements provide unique insights by probing the Fe5 GeTe2 /graphene interface spintronic properties via spin‐dynamics measurements, revealing multidirectional spin polarization. Density functional theory calculations in conjunction with Monte Carlo simulations reveal significantly canted Fe magnetic moments in Fe5 GeTe2 along with the presence of negative spin polarization at the Fe5 GeTe2 /graphene interface. These findings open opportunities for vdW interface design and applications of vdW‐magnet‐based spintronic devices at ambient temperatures. Abstract : The room‐temperature operation of spin‐valve devices using the van der Waals itinerant ferromagnet Fe5 GeTe2 in heterostructures with graphene is demonstrated. Lateral spin‐valve, Hanle spin precession measurements, and theoretical calculations provide unique insights by probing the Fe5 GeTe2 /graphene interface spintronic properties via spin‐dynamics measurements, revealing multidirectional spin polarization.